An updated checklist of the Recent non-marine Ostracoda (Crustacea) of Iran, with a redescription of Eucypris mareotica (Fischer, 1855) - Rasouli, Hamidreza; Scharf, Burkhard; Meisch, Claude; Aygen, Cem (Zootaxa, 2016)
An updated checklist of the extant non-marine Ostracoda of Iran, with 74 species in all, is presented, based on literature and new collections made in May 2011. The occurrence of 19 non-marine ostracod species recovered from 10 localities in May 21–26, 2011 is reported together with ecological data. Eucypris kerkyrensis Stephanides, 1937, Ilyocypris inermis Kaufmann, 1900, Psychrodromus fontinalis Wolf, 1920, and P. olivaceus (Brady & Norman, 1889) are new to the fauna of Iran. Eucypris mareotica (Fischer, 1855) is redescribed and its taxonomic position is discussed. It is shown that E. mareotica—synonymous with E. inflata—does not belong to the genus Eucypris sensu stricto, and even not to the subfamily Eucypridinae; as its characters do not fit any available genus, the species is therefore provisionally left in the genus Eucypris at present. Eucypris mongolica (Daday, 1909) is proposed to be considered an infraspecific variety of E. mareotica. The following new combination is here proposed: Strandesia ambigua (Ghetti, 1972) nov. comb.